Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex]A=2(L+W)\\\\A=2 L+2W\\ \\2W=A-2L\ \ /:2 \\\\W=\frac{A}{2} -\frac{2L}{2}\\\\W=\frac{1}{2}A -L[/tex]
For this case we have the following expression:
[tex] A = 2 (L + W)
[/tex]
From here, we want to clear the value of W.
For this, we follow the following steps:
1) Pass the number 2 dividing:
[tex] (L + W) = \frac{A}{2}
[/tex]
2) Pass the variable L subtracting:
[tex] W = \frac{A}{2} - L
[/tex]
Thus, we observe that we have the equation solved for the variable W.
Answer:
Solving the equation for W we have:
[tex] W = \frac{A}{2} - L [/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.